Justifying Clinical Nudges - Gorin, Moti (The Hastings Center report, 2017)
The shift away from paternalistic decision-making and toward patient-centered, shared decision-making has stemmed from the recognition that in order to practice medicine ethically, health care professionals must take seriously the values and preferences of their patients. At the same time, there is growing recognition that minor and seemingly irrelevant features of how choices are presented can substantially influence the decisions people make. Behavioral economists have identified striking ways in which trivial differences in the presentation of options can powerfully and predictably affect people's choices. Choice-affecting features of the decision environment that do not restrict the range of choices or significantly alter the incentives have come to be known as “nudges.” Although some have criticized conscious efforts to influence choice, we believe that clinical nudges may often be morally justified. The most straightforward justification for nudge interventions is that they help people bypass their cognitive limitations—for example, the tendency to choose the first option presented even when that option is not the best for them—thereby allowing people to make choices that best align with their rational preferences or deeply held values. However, we argue that this justification is problematic. We argue that, if physicians wish to use nudges to shape their patients’ choices, the justification for doing so must appeal to an ethical and professional standard, not to patients’ preferences. We demonstrate how a standard with which clinicians and bioethicists already are quite familiar—the best-interest standard—offers a robust justification for the use of nudges.